2010
DOI: 10.1095/biolreprod.110.085381
|View full text |Cite
|
Sign up to set email alerts
|

Ovine Surgical Model of Uterine Space Restriction: Interactive Effects of Uterine Anomalies and Multifetal Gestations on Fetal and Placental Growth1

Abstract: Intrauterine growth restriction (IUGR) is observed in conditions with limitations in uterine space (e.g., uterine anomalies and multifetal gestations). IUGR is associated with reduced fetal weight, organ growth, and a spectrum of adult-onset diseases. To examine the interaction of uterine anomalies and multifetal gestations, we developed a surgical uterine space restriction model with a unilateral uterine horn ligation before breeding (unilateral surgery). Placentas and fetuses were studied on Gestational Day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(73 citation statements)
references
References 55 publications
6
66
1
Order By: Relevance
“…Interestingly, there was an increase in placental efficiency (i.e., fetal:placental weight) in the PR fetuses. This is consistent with a model of IUGR, in which uterine space is restricted, and this is associated with a higher placental efficiency (51). This suggests that adaptations occur in the placenta of PR fetuses that increase the ability of the placenta to transfer substrates to the PR fetus or that the PR fetus makes adaptations such that the requirement for substrates is reduced.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, there was an increase in placental efficiency (i.e., fetal:placental weight) in the PR fetuses. This is consistent with a model of IUGR, in which uterine space is restricted, and this is associated with a higher placental efficiency (51). This suggests that adaptations occur in the placenta of PR fetuses that increase the ability of the placenta to transfer substrates to the PR fetus or that the PR fetus makes adaptations such that the requirement for substrates is reduced.…”
Section: Discussionsupporting
confidence: 87%
“…This model restricts pregnancy to only one horn (gravid) throughout gestation allowing us to study local pregnancy-specific maternal-fetal vascular function and angiogenesis [25][26][27]. The control pregnant group comprised of sham operated (n = 15) and nonsurgical controls (n = 22).…”
Section: Methodsmentioning
confidence: 99%
“…During pregnancy, these uterine vascular adaptations lead to the rises in UBF which are required to provide for an adequate maternal-fetal vascular interface to meet the nutrient and oxygen demands of the rapidly growing fetus [21]. Using a preconception surgical model, we established a cohort of unilateral ovine pregnancies and demonstrated that rises in UBF as well as uterine vascular adaptations are seen only ipsilateral, but not contralateral, to the fetus and placental unit [25][26][27]. Additionally, we previously reported experimental analyses of the ex vivo uterine artery endothelium (UAendo) and uterine artery vascular smooth muscle (UAvsm) from pregnant versus nonpregnant ewes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also many nonfunctional caruncles (i.e., those that did not participate in induction of formation of a placentome). The number of functional caruncles and placentomes can be altered surgically (Alexander, 1964a) or by restricting the pregnancy to 1 uterine horn (Bazer et al, 1979), but there is compensatory growth of placentomes so that fetal weight is not necessarily affected (Meyer et al, 2010). In fact, we used the unilaterally pregnant ewe model to test the hypothesis that intrauterine crowding would stimulate more caruncles to become engaged with the chorioallantos to form placentomes (Bazer et al, 1979;Gaton et al, 1984).…”
Section: Discussionmentioning
confidence: 99%